Performance Study of Three Parallel Runways at Soekarno-Hatta Airport - Annisa, Tengku (Journal of Transportation Study Forum, 2024)
To improve service quality, Soekarno-Hatta international airport is adding a runway, so that the runway becomes a three-parallel runway. The runway is targeted to be able to accommodate the number of aircraft movements until 2020. This final assignment tries to find out whether the capacity of the planned runway can meet the targets that have been set. In this final project, we will review the distribution pattern of aircraft categories and the distribution of aircraft departure/arrival movements that affect the runway, then a simulation of aircraft movements will be carried out to obtain capacity on the runway. From the final assignment, the percentage distribution results of the aircraft categories used were C: 45% and D: 55%. The distribution of aircraft movements for runway 1 is departure: 59% and arrival: 41%, for runway 2 it is departure: 32.5% and arrival: 67.5% while for runway 3 it is departure: 40% and arrival: 60%. The results of the simulation of movements at peak hour were 124 movements. It is known from the data that peak hour aircraft movements in 2020 were 148 movements. With the results obtained, it was concluded that the aircraft movement target could not be met by adding the runway to a three-parallel runway.